THE ROLE OF NATIONAL TRADITIONS IN THE EDUCATION OF PRESCHOOL CHILDREN - Saidov Jur’at (Web of Journals Publishing, 2024)
Today's young generation is the true owner of their destiny, the creator of their history, the owner of their own national values, acting on the basis of our morals. This article discusses the importance of national traditions in the upbringing of preschool children.
Keywords: ethnic space, system of national values, formation of universal values, development, culture, spirituality, customs, traditions, harmoniously developed generation.